ENDODONTIC ANATOMY OF SECOND MAXILLARY PREMOLARS AND THEIR RELATION TO MAXILLARY SINUS AS INDICATED BY CONE-BEAM COMPUTED TOMOGRAPHY - Cristina Coralia Nistor; Elena Claudia Coculescu; Anca Oana Dragomirescu; Ioana Suciu; Ecaterina Ionescu; Luiza Maria Nicolcea; Dana-Cristina Bratu (Romanian Society of Oral Rehabilitation, 2024)
The aim of this study was to evaluate the root and root canal morphology of maxillary second premolars and their relation to the maxillary sinus in a Romanian population using cone-beam computed tomographic (CBCT) imaging. A total of 280 cone-beam computed tomographic images of maxillary second premolars were obtained from 263 patients who required a preoperative assessment for treatment plan. The number of roots and root canals and root canal configuration were investigated and categorized using Vertucci's criteria and the relationship between the root apices of maxillary second premolars and the floor of the maxillary sinus was studied. The majority of maxillary second premolars were single rooted. The most common configuration was type I, followed by type II Vertucci, for the premolars with 2 canals. The roots of the maxillary second premolars were predominantly outside the maxillary sinus. Maxillary second premolars in this study had a wide range of root and root canal internal anatomy variations.